Chemical Composition of Essential Oil of Pinus nigra subsp pallasiana (Pinaceae) Twigs, From Different Regions of Turkey - Dogan, Gulden; Bagci, Eyup (Taylor & Francis Ltd, 2018)
We used GC and GC-MS systems to analyze the chemical composition of essential oils extracted from twigs of Pinus nigra ant. subsp. pallasiana (Lamb.) Holmboc (Black pine) naturally grown in Turkey. Twig samples were collected from four regions of Turkey (Adana, Adiyaman, Antalya and Elazig) and the twigs were hydrodistilled by clevenger apparatus. Forty three (Adana), 40 (Adiyaman), 29 (Antalya) and 44 (Elazig) components were identified representing 90.7 %, 97.8 %, 98.4 %and 87.7 %, respectively of all extracted oils. The main compounds of oil samples were germacrene D,alpha -pinene, delta-3-carene, beta-pinene, limonene and beta-caryophyllene. Here we discuss chemical differences with reference to forestry products and renewable resources, and we also assess intrapopulational means.
Keywords: Pinus nigra; essential oil; germacrene; alpha-pinene; beta-pinene